Green manufacturing: avaliação do ciclo de vida de processos de usinagem e tubos de alumínio - Firmino, Alessandro Silveira (Universidade Federal de São Carlos, 2020)
Manufacturing processes are performed to convert raw materials into products. To perform these processes, natural resources are consumed and emissions are generated reflecting the potential for adverse environmental impacts. In order to obtain productive systems with less negative impacts on the environment, Green Manufacturing (GM) was emerged. Thus, the concept of GM was used in this dissertation, in which the environmental performance of aluminum pipes’ machining processes was studied. For this, the application of a Life Cycle Assessment (LCA) oriented to the evaluation of two manufacturing processes was organized, based also in the use of a detailed methodology to develop the Life Cycle Inventory (LCI) of the studied processes – the Unit Process Life Cycle Inventory (UPLCI). The application of the UPLCI and the development of the LCA phases, especially the Life Cycle Impact Assessment (LCIA) phase, were carried out through the selection of midpoint impact categories from the ReCiPe 2016 method, and allowed to identify the potential environmental impacts of the studied processes and identify the electricity and the cutting fluid as their main hotspots. With the obtained results and through the performance of sensitivity analysis, future manufacturing scenarios were proposed to reduce the impacts arising from these hotspots. The proposed environmentally benign manufacturing scenario was the suggestion to duplicate the quantity of parts manufactured at each production cycle, moving from three to six machined parts per cycle, and reducing 25% of the raw material surplus to be machined. All of that resulted in important improvements for all the impact categories, enabling reductions in the potential impacts up to 16.47% for the cradle-to-gate life cycle. Further, benefits regarding to classic Production Engineering metrics such as the productivity index and the machine occupancy rate were achieved and resulted into a better eco-efficiency index of the production system up to 23.55%, that will enable the achievement of a more sustainable manufacturing system.
Green manufacturing: life cycle assessment of aluminium pipes’ machining processes
Keywords: ACV; UPLCI; Usinagem; Ecoeficiência; LCA; Machining; Eco-efficiency; Manufatura Ambientalmente Sustentável; Green Manufacturing; ENGENHARIAS::ENGENHARIA DE PRODUCAO